Natural Polysaccharides as Active Biomaterials in Nanostructured Films for Sensing - Eiras, Carla; Santos, Amanda C.; Zampa, Maysa F.; Facundo de Brito, Ana Cristina; Leopoldo Constantino, Carlos J. [UNESP]; Zucolotto, Valtencir; dos Santos, Jose R. (Vsp Bv, 2010)
The search for natural, biocompatible and degradable materials amenable to be used in biomedical/analytical applications has attracted attention, either from the environmental or medical point of view. Examples are the polysaccharides extracted from natural gums, which have found applications in the food and pharmaceutical industries as stabilizers or thickening agent. In a previous paper, however, it was shown that a Brazilian natural gum, chicha ( Sterculia striata), is suitable for application as building block for nanostructured film fabrication in conjunction with phthalocyanines. The films displayed electroactivity and could be used in sensing. In the present paper, we introduce the use of two different natural gums, viz., angico (Anadenanthera colubrina) and caraia (Sterculia urens), as active biomaterials to be used to modification layers, in the form of nanostructured thin films, including the study of dopamine detection. The multilayer films were assembled in conjunction with nickel tetrasulfonated phthalocyanines (NiTsPC) and displayed good chemical and electrochemical stability, allowing their use as transducer elements in sensors for detection of specific neurotransmitters. It is suggested here that nanoscale manipulation of new biodegradable natural polymers opens up a variety of new opportunities for the use of these materials in advanced biomedical and analytical devices. (C) Koninklijke Brill NV, Leiden, 2010
Keywords: Polysaccharides; nanostructured films; nanobiotechnology; dopamine detection